Sponge epizoism in the Caribbean and the discovery of new Plakortis and Haliclona species, and polymorphism of Xestospongia deweerdtae (Porifera) - Vicente, Jan; Zea, Sven; Hill, Russell T. (Zootaxa, 2016)
The new discovery by Vicente et al. (2014) of specialized epizoic symbioses between sponges of the genera Plakortis and Xestospongia revealed the obligate interaction of two new Plakortis spp. associating with Xestospongia deweerdtae and a new Xestospongia sp. In this study we formally describe the two new Plakortis spp. as Plakortis deweerdtaephila sp. nov. (previously reported as Plakortis sp. 1), Plakortis symbiotica sp. nov. (previously reported as Plakortis sp. 2) and describe the new Xestospongia sp. epibiont as Haliclona (Halichoclona) plakophila sp. nov. Plakortis deweerdtaephila associates only with X. deweerdtae, and has very small to large straight diods (24.2–233.7 μm long) and triods (26.4–102.6 μm long) that form large ectosomal circular meshes (114–329 μm diameter). P. symbiotica associates with both X. deweerdtae and H. plakophila, has larger curved diods (71.9–141.8 μm long) and triods (20.4–70.6 μm long) that form smaller ectosomal circular meshes (43–121 μm diameter) than P. deweerdtaephila. Phylogenetic analysis of cox1 and cob gene fragments revealed a strongly supported clade that grouped both Plakortis spp. nov. distantly from any other known Plakortis spp. H. plakophila is described as a thin encrusting veneer of tissue with occasional papillae, so far only found associated with P. symbiotica in La Parguera, Puerto Rico. Phylogenetic analysis of 18S rRNA and cox1 gene fragments place it distantly from any known clade of Haplosclerida. We found a new associated morphotype of X. deweerdtae from Bocas del Toro Panama, which completely overgrew P. deweerdtaephila. In addition, free-living morphotypes from Panama produce larger S-shaped and round bracket shaped strongyles never before observed for this species, leading us to redescribe X. deweerdtae. All X. deweerdtae morphotypes shared >99% sequence homology of cox1, 18S rRNA and 28S rRNA genes with the holotype of X. deweerdtae. This study highlights the highly variable morphological characters of X. deweerdtae influenced by lifestyle and environmental factors. This is also the first time that an obligate symbiosis with a heterospecific sponge is used as a key taxonomic character.